Fellowship program directors and trainees across the United States find parental leave policies to be inconsistent, inaccessible, and inadequate. - Daniel Sabido Jamorabo (Public Library of Science (PLoS), 2021)
Introduction Determine the consistency, accessibility, and adequacy of parental leave policies for adult and pediatric medicine fellowship programs. Methods We administered a 40-question survey to fellowship program directors (PDs) and trainees in adult and pediatric cardiology, hematology/oncology, gastroenterology, and pulmonology/critical care fellowship programs in the United States. We used Chi-square tests to compare proportions for categorical variables and t-tests to compare means for continuous variables. Results A total of 190 PDs from 500 programs (38.0%) and 236 trainees from 142 programs (28.4%) responded. Most respondents did not believe that parental leave policies were accessible publicly (322/426; 75.6%), on password-protected intranet (343/426; 80.5%), or upon request (240/426; 56.3%). The PDs and trainees broadly felt that parental leave for fellows should be 5-10 weeks (156/426; 36.6%) or 11-15 weeks (165/426; 38.7%). A majority of PDs felt that there was no increased burden upon other fellows (122/190; 64.2%) or change in overall well-being (110/190; 57.9%). When asked about the biggest barrier to parental leave support, most PDs noted time constrains of fellowship (101/190; 53.1%) and the limited number of fellows (43/190; 22.6%). Trainees similarly selected the time constraints of training (88/236; 37.3%), but nearly one-fifth chose the culture in medicine (44/236; 18.6%). There were no statistically significant differences in answers based on the respondents' sex, specialty, or subspecialty. Discussion Parental leave policies are broadly in place, but did not feel these were readily accessible, standardized, or of optimum length. PDs and trainees noted several barriers that undermine support for better parental leave policies, including time constraints of fellowship, the limited number of fellows for coverage, and workplace culture. Standardization of parental leave policies is advisable to allow trainees to pursue fellowship training and care for their newborns without undermining their educational experiences.